Preface - Devi Geetha; Sadriddinov Manuchehr; Khalmatjanova Gulchekhra (BIO Web of Conferences)
The overview is devoted to the main directions and results of the IV International Conference on Improving Energy Efficiency, Environmental Safety and Sustainable Development in Agriculture (EESTE2024) held on October 28 - 30, 2024. It describes the main directions and gives the details about the participants and the proceedings.